INDONESIAN MUSLIM IDENTITY CONSTELLATION IN THE DIGITAL MEDIA: Labeling Arrogant Islam by Permadi Arya on Social Media - Perdana Putra Pangestu (AL-TAHRIR, 2021)
Abstract: The emergence of various negative religious prototypes and labels has become an increasingly problematic tempest in Indonesia. Especially in Islam, dedicating meaning to a particular topic and model of the diversity of groups has recently been public hot discussions. The presence of social media creates a constellation of national narratives that have various contents. In this case, the researcher will formulate how the interactions that occur in society, especially on social media, are related to the verdict in the form of symbols addressed to certain religious models. The researcher starts with terms such as “Islam Radikal” and “Islam Arogan” which are specifically used by Permadi Arya in showing his reaction to the public on religious opinions on social media. This study uses a qualitative approach by collecting Permadi Arya’s digital record data on social media as the primary source of the analysis. The data analysis was carried out by conducting collaborative topics on the model diversity of issues with the concept of Cyber Religion and Symbolic Interaction. This study revealed that the contestation to show a certain ideology on social media has also sparked various responses in the form of various identities and stigma attachments. Especially in the term “Islam Arogan” which is directed at Permadi Arya to groups with a ultra-conservative religious and radical model. امللخص :ن شأة النامذج املتنوعة والشعائر الدينية السلبية يكون مشكالت زادت بها الرصاعات يف إندونيسيا. وخاصة يف اإلسالم، يف األيام الجارية إطالق النتيجة للموضوع  املعني ومنوذج خالف املجموعة املعينة يحل محل الحوار الدافئ، فضال بحضور الوسائل اإلجتامعية اإلفرتاضية، يشكل الجدال النيص يف املرحلة الوطنية ذا املحتويات املتعددة. ويف هذا األمر، لخص الباحث كيفية بناء التواصل بني أيدي املجتمع، خاصة يف الوسائل اإلجتامعية، تعلقا بالتحكم يف شكل الرموز الهادفة إىل نوع من املجموعة املتنوعة املعينة. ذهب الباحث إىل مصطلحات يف مثل و »اإلسالم املتطرف« و »اإلسالم الغاضب« ألقاها برمادي أريا يف عرض رده عىل التعليقات الدينية املورودة يف الوسائل اإلجتامعية. اعتمد الباحث فيه املنهج الكيفي باستخدام سرياته الذاتية الرقمية يف الوسائل اإلجتامعية كبيانات أساسية ومصادرها املبدئية. وتحليلها يجري عىل اختالط املوضوع باإلشاعة التنوعية يف ضوء التدين الرقمي والتواصل السياميئ. وحصل هذا البحث نتيجته بكشف أن طريقة النزاع لعرض األفكار الدينية املعينة يف الوسائل اإلجتامعية تشعل نار الردود يف شكل نشاة الهوية والعالمة املتنوعة. خاصة يف مصطلح »اإلسالم الغاضب« الذي ألقاه برمادي إىل املجموعة ذات أسلوب التدين املتشدد و املتطرف.Abstrak: Munculnya berbagai prototipe serta label keagamaan yang negatif menjadi sebuah prahara yang kian problematik di Indonesia. Khususnya dalam agama Islam, pemberian makna terhadap suatu topik dan model keberagamaan kelompok tertentu menduduki porsi perbincangan hangat publik akhir-akhir ini. Terutama dengan hadirnya media sosial berbasis daring, membuat sebuah konstelasi narasi berskala nasional yang mempunyai muatan yang beragam. Dalam hal ini, Peneliti akan merumuskan bagaimana konstruksi interaksi yang terjadi di masyarakat, khususnya di media sosial, terkait dengan vonis berupa simbolsimbol yang dialamatkan pada model keberagamaan tertentu. Peneliti bertolak pada istilah-istilah seperti “Islam Radikal” dan “Islam Arogan” yang secara spesifik dilayangkan oleh Permadi Arya dalam penunjukan reaksinya kepada publik terhadap opiniopini keagamaan di media sosial. Penelitian ini menggunakan pendekatan secara kualitatif dengan penggunaan data rekam digital Permadi Arya di media sosial sebagai basis pokok dalam sumber primer analisis Peneliti. Analisis data dilakukan dengan melakukan kolaborasi topik terhadap isu-isu model keberagamaan dengan konsep Cyber Religion dan Interaksi Simbolik. Penelitian ini berhasil mengungkap bahwasannya kontestasi untuk menunjukkan ideologi keagamaan tertentu di media sosial turut memantik pelbagai respon berupa munculnya identitas dan tempelan stigma yang variatif. Khususnya pada term “Islam Arogan” yang diarahkan Permadi Arya pada kelompok dengan model keberagamaan secara keras dan radikal.